Comparison of microgels, extracellular polymeric substances (EPS) and transparent exopolymeric particles (TEP) determined in seawater with and without oil - Xu, Chen; Chin, Wei-Chun; Lin, Peng; Chen, Hongmei; Chiu, Meng-Hsuen; Waggoner, Derek C.; Xing, Wei; Sun, Luni; Schwehr, Kathleen A.; Hatcher, Patrick G.; Quigg, Antonietta; Santschi, Peter H. (Marine chemistry, 2019)
Extracellular polymeric substances (EPS), produced by microorganisms, are implicated for greatly influencing the fate of environmental contaminants, including oil. Transparent exopolymeric particles (TEP) are gel-like acidic polysaccharide particles that can be stained with Alcian blue, whereas Coomassie stainable particles (CSP) contain proteins and are stained with Coomassie brilliant blue. Marine microgels are reversibly formed from EPS. These terms are often used interchangeably, but they have rarely been measured simultaneously. Mesocosm and bottle experiments provided an opportunity to compare EPS, TEP, CSP and microgels in a water-accommodated fraction (WAF) of oil and seawater (control). Our results reveal that the biopolymers making up EPS, TEP and CSP consisted primarily of polysaccharides and proteins, mostly likely as proteoglycans and glycoproteins. Significant correlations were found between concentrations of TEP-C vs particulate organic carbon (POC), TEP-C vs particulate organic nitrogen (PON), TEP vs EPS, TEP vs CSP, TEP vs carbohydrates, proteins, CSP and carbohydrates, CSP vs proteins, and carbohydrates vs proteins. Chemical analysis of whole particles and colloids yielded both protein and polysaccharides concentrations higher than those in EDTA extraction, thus providing an upper limit of actual EPS contents in the particulate phase. The EPS that was electrostatically held onto particle surfaces (extractable by 1% EDTA) accounted for a minor (~4%) yet relatively constant proportion of TEP. Overall, the concentrations of the three terms ranked in the order of [gels] > [TEP] > [particulate EPS] in the water. Lastly, spectrophotometric methods have limitations in identifying complex or refractory polysaccharides, as evidenced by the comparison between NMR-quantified EPS and the total EPS determined by spectrophotometric methods. This study is the first time these terms were compared in the same sample. They provide useful information when reviewing historical TEP, CSP, EPS data collected field- and laboratory-studies, and provide linkages between them. In addition, they also demonstrate that they could provide complementary information relevant to ecosystem and flux studies. [Display omitted] •EPS, TEP, CSP and microgels are operational measurements of exopolymeric materials•EPS, TEP, CSP and POC correlated well to each other in mesocosm experiments•EPS measured in the 1% EDTA extractable fraction asseses ~4% of TEP•[gels] > [TEP] > particulate EPS in bottle experiments with Gulf of Mexico waters•Spectrophotometric methods underestimate polysaccharide fraction compared to NMR